"You can't touch this": Delivery of inpatient neuropsychological assessment in the era of COVID-19 and beyond. Issue 7 (16th November 2020) - Parlar, Melissa E.; Spilka, Michael J.; Wong Gonzalez, Daniela; Ballantyne, Elena C.; Dool, Catherine; Gojmerac, Christina; King, Jelena; McNeely, Heather; MacKillop, Emily
Abstract: Objective: The COVID-19 pandemic is a global health crisis that has created sudden and unique challenges within the field of clinical neuropsychology. Adapting neuropsychology services using teleneuropsychology models (e.g. video or telephone assessments) may not always be a viable option for all providers and settings. Based on the existing teleneuropsychology literature, we propose a "contactless" evidence-based inpatient test battery to be used for in-person assessments amenable to physical distancing. Method: In addition to the proposed test battery, we suggest a decision-making workflow process to help readers determine the appropriateness of the proposed methods given their patients' needs. Considerations for special populations (i.e. seniors, patients with brain injury, psychiatric patients), feedback, limitations of the proposed physical distancing approach, and future directions are also discussed. Conclusions: Our aim is that the suggested teleneuropsychology-informed battery and model may inform safe and practical neuropsychological inpatient assessments during the COVID-19 pandemic and other situations requiring contact precautions for infection prevention and control.